Senior Secondary School Biology Teachers’ Perspectives on Factors Affecting Girl-Child Education in Kwara North Senatorial District, Nigeria - Mohamed, Idris; Okere, Chibueze Sylvester; Ozioko, Sylvester Ugwu; Anuniru, Chinazom; Ngumah, MaryJoan Obianuju; Onyeanuna, Ngozi Ihechiluru; Onyenoro, Peace; Nwoko, Ogadinma Ekwy; Ahmed, Mulka (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
The low enrollment of girls in secondary schools across the Kwara North senatorial district has become a significant challenge to educational progress in the region. Some educators attribute this issue to parental restrictions that prevent girls from pursuing secondary education. This study investigated the perspectives of senior secondary school biology teachers on the factors affecting girl-child education in Kwara North, Nigeria. A descriptive survey design was adopted, with a target population of 270 biology teachers from Edu, Moro, and Patigi Local Government Areas of Kwara State. Using a convenience sampling method, participants were selected for the study. Data were gathered through a structured questionnaire titled "Senior Secondary School Biology Teachers’ Views on Factors Affecting Girl-Child Education." Descriptive statistics, including frequency counts and percentages, were used to analyze the research questions, while chi-square tests were applied to test the hypotheses at a 0.05 significance level. The results indicated that parental perceptions of girls as financial contributors to their households significantly impact their educational opportunities. The study concluded that socio-cultural factors play a fundamental role in shaping girl-child education in Kwara North, Nigeria. To address this challenge, it was recommended that the government implement free education at all levels to ensure that children from low-income families have access to schooling. Furthermore, strong legal measures should be enacted to eradicate discrimination against girls in education, with strict penalties, including imprisonment, for those who deny them their right to quality education.